2014
DOI: 10.1039/c4ra08226e
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and corrosion behavior of Co and Co–P coatings electrodeposited from chloride bath

Abstract: Co–P coatings with low and high phosphorous contents are electrodeposited using direct current (DC) and pulse current (PC) methods from cobalt chloride baths.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(15 citation statements)
references
References 43 publications
1
14
0
Order By: Relevance
“…In the deposited Co-P coatings, the components of the alloy were dense and uniform, for the reason that P dispersed in the cobalt metal during the formation of solid supersaturated solution. Thus, the alloy showed higher corrosion potential [10]. Furthermore, in the amorphous coatings of Co-P coatings as deposited, because there were no grain boundaries, the corrosion attacks seem to be lower [20]; thus, Co-P coatings were endowed with outstanding corrosion resistance.…”
Section: Effect Of Heat Treatment On the Corrosion Resistance Of Co-pmentioning
confidence: 94%
See 1 more Smart Citation
“…In the deposited Co-P coatings, the components of the alloy were dense and uniform, for the reason that P dispersed in the cobalt metal during the formation of solid supersaturated solution. Thus, the alloy showed higher corrosion potential [10]. Furthermore, in the amorphous coatings of Co-P coatings as deposited, because there were no grain boundaries, the corrosion attacks seem to be lower [20]; thus, Co-P coatings were endowed with outstanding corrosion resistance.…”
Section: Effect Of Heat Treatment On the Corrosion Resistance Of Co-pmentioning
confidence: 94%
“…It has been demonstrated that a certain amount of surfactant in solution could result in more smooth coatings. Ezhilselv et al [10] measured the potentiodynamic polarization curve of Co-P coatings, which revealed that coatings deposited under pulse current showed better corrosion resistance than that deposited under direct current. A similar result was obtained by Kosta et al [11].…”
Section: Introductionmentioning
confidence: 99%
“…Co-P coatings have been identied as suitable materials for replacement of environmentally-unfriendly hard chromium due to their excellent wear resistance, corrosion resistance and high thermal stability. [1][2][3][4][5] The properties of Co-P coatings are mainly inuenced by the P content and phase structures of alloy coatings. It was reported that Co-P coatings with high P content and amorphous structure exhibit excellent corrosion resistance.…”
Section: Introductionmentioning
confidence: 99%
“…Among these variables, current mode is a exible and efficient variable to modify the P content and phase structures of alloy coatings. Ezhilselvi et al 1,7 demonstrated that the Co-P coatings deposited by PC method have better corrosion resistance than those by DC method. Pulse current (PC) and pulse reverse current (PRC) are the two most common types of pulsed method.…”
Section: Introductionmentioning
confidence: 99%
“…However, the effect of alloying non‐metal like phosphorous to improve the properties of cobalt‐based alloys is a topic of recurring interest. Codeposition of phosphorous with cobalt from various bath conditions using different plating techniques has also gained equal attention owing to its improved microhardness, magnetic properties, thermal stability and high corrosion resistance of the coatings . In most of these above mentioned studies, individual effects of P codeposition and W codeposition with cobalt and their properties have been investigated.…”
Section: Introductionmentioning
confidence: 99%